A Risk Prediction Model for Breast Cancer Based on Immune Genes Related to Early Growth Response Proteins Family - Zhou, Xin; Zhang, Fang-yuan; Liu, Yan; Wei, Dong-xin (Frontiers in Molecular Biosciences, 2021)
Early growth response proteins (EGRs), a transcriptional regulatory family comprising of EGR1, EGR2, EGR3 and EGR 4, are reportedly involved in a vast array of functions. However, EGRs, as a whole, are rarely studied in patients with breast cancer. Our research was performed by using public datasets. The results demonstrated that, except EGR4, the other EGRs were differentially expressed genes in breast cancer. Then we explored the prognostic value of EGR family, higher expression levels of EGRs indicating better OS and DFS, except EGR4. At DNA level, however, neither DNA methylation status nor genetic alterations of EGRs were contribute to the prognostic significance. KEGG pathway analysis revealed that EGRs were involved in several immune-related functions. Afterword, we evaluated the correlation between EGRs and immune system before establishing a risk prediction model with a 14-gene immune signature associated with EGRs, a prognostic nomogram predicting individuals’ 1- ,3- and 5-year survival probabilities. Our findings showed evidence of EGR’s implication in tumor immunity, suggesting that they may be potential immunotherapeutic targets for breast cancer and the immune signature is a promising prognostic biomarker in breast cancer.